Knowledge, attitude and practices used in the control of Striga in maize by smallholder farmers of western Kenya - Nambafu, G.N.; Onwonga, R.N.; Karuku, G.N.; Ariga, E.S.; Vanlauwe, Bernard; Roing de Nowina, K. (2014)
The production of maize is constrained by parasitic weeds, particularly Striga. A study was carried out to document farmers’ knowledge, attitude and practices on Striga control among smallholder farmers across three districts: Kisumu West, Busia and Teso South of Western Kenya. A multistage sampling technique was used to select the locations and farmers to be interviewed. A semi structured, open and closed ended questionnaire was administered leading to field experiment. Besides village meetings (39.2%), farmers got informed on farming methods under Striga weed farms and its control technologies through neighbours (2.5%), workshops and trainings (5.0%), field schools (3.7%), media (7.5%) and extension agents (10.8%). The attitudes of farmers towards Striga control varied but frequently cited: long term viability of the Striga seed (12.5%), difficult to control sharing of farm tools (10.8%), expensive technologies (13.3%), lack of adequate information (18.3%), labour intensive (15.0%), large farms for use of push and pull technology (1.7%) and time consuming (12.5%). Framers used various Striga control practices but traditional methods (25%) were among the most used (25%). Concerted effort involving researchers, extension agents and private sector are, therefore, required for wide scale dissemination and adoption of the existing modern control technologies.